Psychology and social policies: A historical overview of psychological practice in Brazilian Public Health (2014)
This article examines the evolution of public health policies in Brazil after 1985, when the democratic transition process began at the end of the military rule, and their impact on the professional practice of psychologists. Brazilian social policies of this period and the construction and development of the Unified Healthcare System – SUS (the Brazilian National Health System) are reviewed, as the context for the discussion of the inclusion of psychologists into public health. Issues such as the suitability of traditional clinic models of practice to public health services, questions concerning the academic training and the limits imposed by social policies for the practice are discussed.